The Apocryphon of John : Synopsis of Nag Hammadi Codices II,1 - III,1 and IV,1 with BG 8502,2 - Wisse, Stefanie, (Nag Hammadi and Manichaean Studies ;, 1995)
This synopsis of the Apocryphon of John presents the four Coptic text (NHC II,1; III,1 and IV,1; with BG 8502) in parallel columns with English translations in similar arrangement beneath the Coptic text. Important parallel texts are included in an appendix. The volume also contains a research bibliography on the Apocryphon of John and an index of Coptic and Greek words.